Puerarin facilitates osteogenesis in steroid-induced necrosis of rabbit femoral head and osteogenesis of steroid-induced osteocytes via miR-34a upregulation. (July 2021) - Jiang, Xin; Chen, Wenjing; Su, Hang; Shen, Fuguo; Xiao, Wenlong; Sun, Wencai
Highlights: Puerarin reversed the effect of dexamethasone on the rabbit osteoblast. The viability of rabbit osteoblasts was decreased by Dex, but increased by puerarin. Puerarin promotes osteoblastic differentiation of osteoblasts via upregulate miR-34a. Abstract: The present study investigated the effect of puerarin on promoting the osteogenesis in steroid-induced necrosis of the femoral head (SONFH). New Zealand rabbits were administrated with horse serum and methylprednisolone (MPS) for establishing SONFH in vivo model, which was then treated with puerarin treatment. Histo-morphological changes in the femoral head were examined by hematoxylin-eosin staining. Osteoblasts were isolated from healthy rabbits and treated by individual or combined administration of dexamethasone and puerarin. Osteoblast viability was measured by CCK-8 assay. Mineralized nodule formation was evaluated by alizarin red assay. Expressions of RUNX family transcription factor 2 (RUNX2), Type-I collagen α 1 (COL1A1), ALP and miR-34a in the femoral head were determined by qRT-PCR and Western blot. Puerarin attenuated the effect of SONFH on promoting histopathological abnormalities and counteracted SONFH inhibition on the expressions of ALP, RUNX2, COL1A1 and miR-34a in the rabbits. Rabbit osteoblasts were successfully isolated, as they showed red mineralized nodules. Dexamethasone exposure decreased osteoblast viability, which was increased by puerarin treatment. Furthermore, puerarin treatment attenuated dexamethasone-induced inhibition on the viability, osteoblastic differentiation, and the expressions of ALP, RUNX2, COL1A1 and miR-34a in the osteoblasts. Puerarin facilitated osteogenesis of steroid-induced necrosis of rabbit femoral head and osteogenesis of steroid-induced osteocytes via miR-34a upregulation.